2006
DOI: 10.4000/vertigo.2038
|View full text |Cite
|
Sign up to set email alerts
|

Impact de la variabilité climatique sur les ressources hydriques des bassins de N’Zo et N’Zi en Côte d’Ivoire (Afrique tropicale humide)

Abstract: Cette étude a pour objectif de montrer l’impact de la variabilité climatique sur les ressources en eau des bassins versants du N’zo et du N’zi. L’indice centré réduit montre une grande variabilité interannuelle de la pluie qui s’organise en une alternance de phase humide (1930-1966 pour le N’zo et de 1930-1968 pour le N’zi), de phase sèche (1967–1993 pour le N’zo et 1969-2000 pour le N’zi) et d’une nouvelle phase humide de 1994 à 2000 uniquement pour N’zo. Le long déficit pluviométrique a provoquée une baisse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
20

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 3 publications
5
39
0
20
Order By: Relevance
“…The impact of these modifications of rainfall regime is translated in rainfall deficits ranging from 12 to 22%. These results are in conformity with many other authors' studies in African subregion in whose the present study is noted ( [14]; [9]), particularly in Côte d'Ivoire ( [15] ; [16] ; [17]) whose were obtained some breaks around seventies years (1970).…”
Section: Hydroclimatic Variability Of Watershedsupporting
confidence: 94%
See 1 more Smart Citation
“…The impact of these modifications of rainfall regime is translated in rainfall deficits ranging from 12 to 22%. These results are in conformity with many other authors' studies in African subregion in whose the present study is noted ( [14]; [9]), particularly in Côte d'Ivoire ( [15] ; [16] ; [17]) whose were obtained some breaks around seventies years (1970).…”
Section: Hydroclimatic Variability Of Watershedsupporting
confidence: 94%
“…This increase of depletion coefficient has been signaled on some Ivorian river by some authors whom [15] at Flampleu station in the west area on Cavally watershed and [23]. In the same ideas, [16] and [24] noted an increase of depletion coefficient in N'zi watershed. For the last author, depletion coefficient ranged between 2.78 10 -2 j -1 and 3.91 10 -2 j -1 before 1968, year identified like break year in hydrometric time series.…”
Section: Depletion Of Rivers Network Volumes Of Water Mobilized and mentioning
confidence: 62%
“…Several studies have been carried out in the transboundary river basin of Sassandra concerning the assessment and management of water resources [15][16][17][18][19][20][21][22], particularly, Ardoin et al [19], Rescan, [20] and Yao [22], who used the Génie Rural à 2 paramètres Mensuel (GR2M) hydrological model. The works of Ardoin et al [19] and Rescan [20] showed that the Sassandra River runoff and water availability would increase from 10 to 13% during the first half of the 21st century (Horizon 2050) before decreasing at the Horizon 2080 when compared to the reference period 1971-1995.…”
Section: Introductionmentioning
confidence: 99%
“…In this country, the impacts of climate change have led to recurrent droughts, changes in rain amount distribution, reduction of arable land, coastal erosion, and flooding [12]. Many studies on the impacts of climate variability were carried out in Côte d'Ivoire [13][14][15][16][17][18]. Few studies have been conducted to investigate the impact of climate change on the water resources in the Bandama basin, despite the increase in water requirements for water supply of populations, agriculture, livestock, mining, and hydroelectric dams.…”
Section: Introductionmentioning
confidence: 99%